Perancangan Aplikasi Kasir Studi Kasus di Toko Hikmah - Rahmi Darnis; Fiki Khoirunisa (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2023)
The development of information technology in the field of business has been widely applied and is able to provide capabilities which greatly helps the activities of a company. One technology that can be applied is a sales information system or cashier application. The wisdom store is one of the shops engaged in the retail sector that sells Office Stationery, currently the wisdom shop still implements a manual system for sales transactions, but the manual system is considered to be no longer effective considering the large number of transactions that occur per day so a cashier application design is needed. which can be used by wisdom shops in services, the design of this application uses the PHP programming language with the MySql database and in system development will use a prototype model. The design of the cashier application at the Wisdom store is able to help the shop in serving customers faster, especially in the purchase queue, this cashier application can also help the Wisdom store in managing stock of goods and providing more structured sales reports.